Medidas alternativa a la prisión por falta de pago en las pensiones alimenticias, en el Juzgado Sexto de la Niñez y Adolescencia del cantón Santa Rosa, año 2011. - Granda Calderón, Vanessa Estaphania (2015)
This research work devotes much of its development to address what constitutes and concerns the administration of justice, especially the constitutional reforms governing prison for non-payment obligor , aspects and nuances , with realistic and positive way to highlight how valuable , good and wrong and also what our poor legal framework in Ecuador with accurate, sufficiently broad and democratic arguments.